The Prevalence of Corruption in Society as Depicted in Selected Xitsonga Poems: A Critical Discourse Analysis - Shirindzi, Lebogang Steven; Maluleke, Ndzalama (Journal of Literary Studies, 2025)
Corruption is prevalent in many spheres of life today. Media platforms such as radio, newspapers, and television, as well as electronic platforms like Facebook and X frequently discuss various forms of corruption in both the public and private sectors. Similarly, literature, essays, and other literary publications often address numerous types of corruption. This article examines how language is employed to represent various forms of corruption in selected Xitsonga poems. This study employs the critical discourse analysis (CDA) approach to investigate how language in selected Xitsonga poems reveals underlying power relations, ideological positions, and social structures associated with corruption. Poems depicting corruption have been selected from various poetry anthologies and critiqued to illustrate the types of corruption identified by Xitsonga poets. The article finds that poets are concerned and worried about the corruption taking place within Vatsonga communities. In conclusion, this article demonstrates how society, through the eyes of poets, feels about corruption.